Shielding against on-off attack pattern in a MANET through a trust computation scheme leveraging the behavioural consistency. (8th July 2021) - Samreen, Shirina
The evolution of security mechanisms for defending a mobile ad hoc network (MANET) is challenged through intelligent strategies employed by the attackers. The current research involves the design of a robust trust management framework (TMF) which protects the network against an attack pattern termed as on-off attack. Each dimension of the attack vector corresponding to packet droppers and dishonest recommenders employing the on-off attack pattern is countered through an individual dimension of the multi-dimensional trust vector termed as forwarding consistency trust and recommendation consistency trust respectively. The efficiency of proposed scheme in reducing the packet loss is analysed through network simulation using NS-2 under different attack scenarios. It is found that incorporation of behavioural consistency in the trust computation plays a very significant role in maintaining the network performance in the presence of on-off attackers by improving the packet delivery fraction from 71% to 85% and the detection ratio from 70% to 95% respectively.